Paul on the human vocation: reason language in Romans and ancient philosophical tradition - Dürr, Simon (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche / Beihefte, 2021)
This book offers a new explanation for Paul’s puzzling use of λογικὴ λατρεία (Rom 12.1). Based on a detailed investigation of ancient philosophical parallels, it argues that Paul here alludes to discourse on the role of human beings in the cosmos, which he sees fulfilled in Christ-followers in particular. It charts the implications of this interpretation for reading Romans and contributes to a possible integration of Paul’s theology and ethics